Hubungan Asupan Zat Gizi Makro dengan Status Gizi Remaja di SMP Negeri 2 Kota Jambi Tahun 2024 - Sutrawanti, Linda; Wulansari, Arnati; Jeki, Andicha Gustra (3031-8572, 2024)
Adolescents are a group that is prone to nutritional problems, both malnutrition and overnutrition. One of the factors that can affect the nutritional status of adolescents is the intake of macronutrients and fibre. According to the 2018 RISKESDAS report, 7.6 per cent of the population in Jambi Province was undernourished and 14.3 per cent was overnourished. The aim of this study is to determine the relationship between macronutrient and nutritional status of adolescents in SMP Negeri 2 Jambi City in 2024. This type of research is a quantitative study with an analytical observational design and cross-sectional design. The research was conducted in SMP Negeri 2 Jambi City in May 2024. The population was students and female students in class VII and class VIII as many as 480 adolescents. The sampling technique used Proportional Random Sampling as many as 80 adolescents. Data collection on macronutrient was done by interview using a 3x24-hour food recall form and nutritional status using measurements of body weight and height calculated by IMT/U. Statistical analysis was univariate and bivariate using the chi-square test. The results showed that adolescents had normal nutritional status (62.5%) and abnormal nutritional status (37.5%) and adequate macronutrient intake (>50%). There was a significant relationship between macronutrient intake and adolescent nutritional status (p-value = 0.000).